(3MGTjI Ydi TQM GdTeSjIs - (3GdjROj, GdjROj, YHO Gddg Hf GdMSjf, (B1015(3g` (B1606(3es ((3eGRfOQGfjs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg, GaJJM HMeO Gddg HYO GdJSejI, GHJOC HNjQ GdcdGe hGbJOGA HMOjK NjQ GdCfGe Ydjg hBdg GdUdGI hGdSdGe, aEf bdJ MOjKs
(3BNQgG (B:s
(3BNQgG(B: (3bhdg(B: (3EfeG GdWQjb Edi (B.. (3Ydi GdNdb, Gj Gdjbjf Ef cGf (B.. (3YdeG fXQjGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B4: 80s
(3GdPQjYI, L (B6: 27(3, (B28s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs